Performance and Return to Sport After Meniscal Repair in Professional Baseball Players. Issue 6 (21st June 2022) - Erickson, Brandon J.; Chalmers, Peter N.; D'Angelo, John; Ma, Kevin; Rowe, Dana; Cohen, Steven B.; Dugas, Jeffrey R.
Background: Meniscal repair is an effective treatment option for certain meniscal injuries to preserve meniscal function and limit the progression of knee osteoarthritis. Outcomes after meniscal repair in professional baseball players are not well documented. Purposes/Hypothesis: The purposes of this study were to determine performance and return to sport (RTS) in professional baseball players after meniscal repair and compare the results of medial versus lateral meniscal repair. It was hypothesized that there would be a high RTS rate, with no difference in the rate or timing of RTS between players who underwent medial versus lateral meniscal repair. Study Design: Cohort study; Level of evidence, 3. Methods: All professional baseball players who underwent meniscal repair between 2010 and 2017 were identified using the Major League Baseball Health and Injury Tracking System database. Descriptive information and performance data (before and after injury) for each player were recorded. The rate and timing of RTS were then compared between players who underwent medial versus lateral meniscal repair. Results: Included were 31 patients (mean age, 24 ± 3 years). There were 6 players (19%) who had failed repair, underwent subsequent meniscectomy within 2 years of meniscal repair, and were thus excluded from the performance analysis. Of the remaining 31 players, 68% returned to the same or a higher level of play, and 6% of players returned to a lower level of play. Most repair procedures (60%) were performed using the all-inside technique, and 72% of players underwent lateral meniscal repair. The mean time missed was 187 ± 67 days, and the mean time to RTS at full competitive play was 209 ± 84 days. There were no significant differences in the rate or timing of RTS between players who underwent medial versus lateral meniscal repair ( P ≥ .999 and P = .574, respectively). Pitchers saw a decrease in usage but no change in performance after meniscal repair. For batters, most metrics were unchanged, but there was a significant decrease in base stealing and on-base percentage after surgery. Conclusion: The RTS rate after meniscal repair in Major League Baseball players was 74% at a mean of 209 days; 19% of players had failed repair and underwent subsequent meniscectomy within 2 years of repair. No difference in the rate or timing of RTS was observed between players who underwent medial versus lateral meniscal repair.